Clinical features and predictors of in hospital mortality in patients with intra cerebral haemorrhage - Agarwal, Rajat K.; Kulshreshtha, Dinkar; Maurya, Pradeep K.; Singh, Ajai K.; Thacker, Anup K. (International Journal of Research in Medical Sciences, 2016)
Background: Intracerebral haemorrhage (ICH) accounts for 15-20% of all strokes and is associated with significant morbidity and mortality. The present study was done to assess the risk factors for ICH and determine the factors responsible for poor outcome in ICH. Methods: Consecutive patients of ICH were assessed for modifiable and non-modifiable risk factors, followed by detailed examination with emphasis on ICH score and CT scan findings. Results: There were 200 patients with ICH; 108 males and 92 females. The prevalence of ICH was maximum in the age group of 61-70 years (34%). Hypertension was present in 68% of the patients and was the single most important modifiable risk factor. The most common presenting symptom was altered sensorium present in 58% patients. The mean hematoma volume in our study was 44+/-45 cm3. 45 patients with a GCS <5 and both the patients with ICH score 5 expired. On multivariate analysis, there was a significant correlation of mortality with GCS and hematoma volume. Conclusions: Hypertension is the commonest risk factor for ICH. Patients with a low GCS score, large hematoma volume and a higher ICH score have a poor prognosis and higher probability of mortality.